Op Art and Industrial Design - Manaia, João (Convergences - Journal of Research and Arts Education, 2023)
In October of 1964, the Time Magazine coined the term Op Art, describing a new style of art, which was a generator of optical illusions. Op Art, also called Optical Art is characterized by the use of geometric patterns and distortions that generates specific perceptual responses, having dynamic qualities which provoke optical illusions and movement sensations that end up involving the body itself, that feels and responds to a stimulus. In the mid-1960s, Op Art’s popularity spread to many objects of everyday life, influencing the product design. In this article, Op Art is contextualized, the main optical effects of Op Art used by product designers are described and analysed, by using visual examples. These include: the moiré pattern, afterimages, Hermann grid and spatial distortions.